2019
DOI: 10.1002/jts.22374
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Relations Among Peritraumatic Posttraumatic Stress Symptoms: An Experience Sampling Study During Wartime

Abstract: The associations among peritraumatic posttraumatic stress symptoms (P‐PTSS) in the immediate aftermath of trauma exposure, including those in the posttraumatic stress disorder clusters of intrusions, avoidance, negative cognitions and mood (NCM), and arousal, might indicate mechanisms through which enduring PTSD develops. During a period of war, exposed participants (N = 181) were sent twice‐daily questionnaires for 30 days via smartphone. We repeatedly assessed the predictive associations between the P‐PTSS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
(79 reference statements)
0
14
0
1
Order By: Relevance
“…However, the speed with which these symptoms affect one another is likely faster than a single day. A recent study demonstrated that the relation between the clusters of PTSD varies depending on the frequency with which they were assessed (Gelkopf, Pickman, Carlson, & Greene, ). Future work should consider assessing symptoms multiple times per day.…”
Section: Discussionmentioning
confidence: 99%
“…However, the speed with which these symptoms affect one another is likely faster than a single day. A recent study demonstrated that the relation between the clusters of PTSD varies depending on the frequency with which they were assessed (Gelkopf, Pickman, Carlson, & Greene, ). Future work should consider assessing symptoms multiple times per day.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is part of a larger study conducted during and following the 2014 Israel–Gaza war (Gelkopf, Lapid Pickman, Carlson, & Greene, 2019; Gelkopf et al, 2017; Greene, 2018; Greene, Gelkopf, Epskamp, & Fried, 2018; Greene, Gelkopf, Fried, Robinaugh, & Lapid Pickman, 2020; Greene et al, 2017; Lapid Pickman, Greene, & Gelkopf, 2017). During this 50‐day conflict, more than 4500 rockets and mortar shells were fired from Gaza on Israeli communities and Israel conducted air and ground operations in Gaza.…”
Section: Methodsmentioning
confidence: 99%
“…While ways of dealing with trauma differ greatly between individuals, in large part they tend to relegate or even forget so as to repress what has a more painful meaning. Subsequently, this will have important consequences for the future: fear, terror, anger, frustration, helplessness, depression, introversion, mistrust, hypervigilance, repression, dissociation (Eisen & Goodman, 1998), and even "false memories" (Ackil & Zaragoza, 1998;Arditte Hall et al, 2019;Brainerd & Reyna, 1996;Gelkopf et al, 2019).…”
Section: The Memory Of Traumatic Eventsmentioning
confidence: 99%